PUBLIKASI WACANA MULOKULTURALISME DI KORAN HARIAN FA JAR - la sakka (Al-Qalam, 2007)
This research was conducted in Makassar, South Sulawesi. Focus studyis Fajar dayly Newspaper. This research aims to describe the role ofmass media especially Fajar Newspaper in socializing multiculturalismidea. This research use qualitative method where data was collected byusing interview and article searching, and then analyzed by criticaldiscourse analysis (CDA).This research indicates that the role of mass media in socializingmulticulturalism issue is quite effective, even not yet maximal becauseof still appearance deflect in accommodating stakeholder